STRATEGI PONDOK PESANTREN DALAM MEMBENTUK KARAKTER SANTRI BERBASIS PESANTREN - Natranila, Reva; Nurhasikin, Siti; Rozi, Rozi (STAI Darul Qalam Tangerang, 2023)
Along with the skills required by oneself, society, nation, and State, education is a quality that contributes to the development of good international relations. If this law is to be well understood, character education is included. Pondok Pesantren is different from other educational institutions because it is run by Muslims. Regarding the elements of education and the education system, the education and teaching methods used in this Islamic boarding school combine traditional and modern approaches, so it is called comprehensive. The Sorogan and Weton methods were used to carry out the education and teaching of the Yellow Book, although a normal school system was created. A person's character is a quality that includes their values, talents, moral capacity, and knowledge to overcome obstacles and problems. Character is shaped by a person's habits, including the way he acts and the things he often says to others. Character and character are what distinguish one person from another. According to Islamic teachings, developing one's character requires developing one's personality within a certain period of time, i.e. through the growth of moral principles. This process cannot be completed quickly or suddenly. The personality of students is influenced by inhibiting factors and supporting factors. The first is divided into two categories: internal and external. The first includes technological advances and the environment of Islamic boarding schools close to rice fields, as well as innate family factors such as laziness and boredom